Odpowiedzi

2010-04-11T19:11:50+02:00
Oblicz wartość liczbową wyrażenia dla x=½
2(5x² +4) + (2x-3)(2x+3)- 2(3x²- 1)+ 3(1- 2x²)2 =
=2[5*(1/2)²+4]+(2*1/2+3)(2*1/2-3)-2[3*(1/2)²-1]+3[1-2*(1/2)²]2=
=2[5*1/4+4]+[(2*1/2)²-3²]-2[3*1/4-1]+3[1-2*1/4]2=
=2[5/4+4]+[1-9]-2[3/4-1]+3[1-1/2]2=
=5/2+8-8-3/2+2+(3-3/2)2=
=3+6-3=6
Jesli na samym koñcu jest po nawiasie razy 2.
2010-04-11T19:12:36+02:00
2(5*1/2² +4)+(2*1/2²+3)-2(3*1/2²-1)+3(1-2*1/2²)2=2(5*1/4+4)+(2*1/4+3)-2(3*1/4-1)+3(1-2*1/4)2=2(1i1/4+4)+(2+3)-2(3/4-1)+3(1-2)2=2*5i 1/4+5-2(-1/4)+3(-1)2=10,5+5+1/2+(-3)2=16-6=10

licze na naj